2017
DOI: 10.1177/2329490617723115
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Textual Cues on First Impressions of an Email Sender

Abstract: The present study experimentally manipulated the gender of an email sender, closing salutation, and sending mode (i.e., email sent via desktop computer/laptop as compared with email sent via a mobile device) to determine if these specific cues influence first impressions of the sender’s competence, professionalism, positive affect, and negative affect. Although no effect of sending mode was found, closing salutation influenced perceptions; females were viewed as less professional when using “Thanks!” as oppose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…One experiment revealed that actors were perceived as more professional when their email signatures included social media information, and less professional when they included religious quotes (Hailpern, Huber, & Calvo, 2020). Marlow, Lacerenza, and Iwig's (2018) experimental study that manipulated email closing statements and gender also revealed some valuable insights. Although women were largely viewed as more professional than men on average, women were viewed as less professional when closing their email with "Thanks!"…”
Section: Figure 1 Virtual Impression Management Behavior Publications...mentioning
confidence: 99%
See 1 more Smart Citation
“…One experiment revealed that actors were perceived as more professional when their email signatures included social media information, and less professional when they included religious quotes (Hailpern, Huber, & Calvo, 2020). Marlow, Lacerenza, and Iwig's (2018) experimental study that manipulated email closing statements and gender also revealed some valuable insights. Although women were largely viewed as more professional than men on average, women were viewed as less professional when closing their email with "Thanks!"…”
Section: Figure 1 Virtual Impression Management Behavior Publications...mentioning
confidence: 99%
“…Targets’ expectations about the actor, often based on stereotypes of the sender’s demographics, are the second moderating component of our framework, represented in the second box in the top middle of Figure 2. Our review thus far has highlighted several such effects, illuminating how expectations stemming from an actor’s relative status (Harmon-Jones et al, 2009; Kalman & Rafaeli, 2011; Muir et al, 2017; Sherblom, 1988; Walther, 2007) and gender (Marlow et al, 2018) moderate virtual impressions. Two additional studies speak to the association between actor gender and virtual interaction expectations.…”
Section: A Virtual Impression Management Frameworkmentioning
confidence: 99%
“…Not surprisingly, most (48.4%) pedagogical attention to communication practices dealt with the specific communication technology used. A total of 44 articles examined both traditional communication formats, such as text documents (Bremner, 2014; Decock et al, 2020; Diaz, 2013; Duncan & Hill, 2014; Koskela, 2018; Maier & Anderson, 2014; Nell et al, 2018) and meetings (Baraldi, 2013; Ewing et al, 2019; Nielsen, 2013; Scott et al, 2013; Tiitinen & Lempiälä, 2022), and formats deemed new, including electronic and social media (Bülow et al, 2019; Hastings & Payne, 2013; Jameson, 2014; Jansen & Janssen, 2013; Kiddie, 2014; Machili et al, 2019; Macnamara & Zerfass, 2012; Marlow et al, 2018; Moore, 2019; Rapanta & Cantoni, 2017; Stephens & Barrett, 2016; Turnage & Goodboy, 2016), internal communication platforms (Anders, 2016; Aten & Thomas, 2016; Cardon & Marshall, 2015; Cowan & Horan, 2021; Darics, 2014, 2020; Gode, 2019; Madsen, 2016, 2017; Pazos et al, 2013; Porter, 2017; Rollins & Lewis, 2012; Uysal, 2016), cell phones (Washington et al, 2014), and teleconferencing (Halbe, 2012). Several authors addressed the increasing importance of interpersonal communication across various settings (Bradley & Campbell, 2016; Hynes, 2012; Jian & Dalisay, 2018; Mazzei et al, 2012; Van De Mieroop & Vrolix, 2014).…”
Section: An Analysis Of the Rhetorical Evolution In The Business Comm...mentioning
confidence: 99%
“…Z namenom zagotoviti dosledno ocenjevane e-pošte v celotni raziskavi, smo osnovnim lestvicam dodali konkretne primere iz e-pošte. Kim et al, 2016;Marlow, Lacerenza, & Iwig, 2018) Subject line 0 -no subject line 1 -irrelevant subject line 2 -relevant subject line, not very informative 3 -relevant, clear and concise description of the purpose (Kim et al, 2016) Message body…”
Section: Marijan Pogačnikmentioning
confidence: 99%